Potency of Kalludaikudori Maththirai, a herbo mineral Siddha formulation in the management of Kalladaippu Noi (Urolithiasis): a drug review - Janani, S.; Niruba, K. (Department of Shalya Shalakya,Gampaha Wickramarachchi Ayurveda Institute,University of Kelaniya,Sri Lanka, 2017)
Siddha medicine is one of the oldest medical systems in the world. Siddha system is the science which takes human and nature as part of closed system. Siddha insists on leading a healthy life both physically and mentally by keeping pace with the laws of nature. Siddhas have classied 4448 diseases, based on the three humoral pathologies. Among them Kalladaippu Noi is classied under Neerinai Aukkal Noigal. According to Siddha dietary factors play a vital role in the formation of Kalladaippu Noi. Also Pitta humor is said to be the major causative factor of this disease. Many formulations are indicated for Kalladaippu Noi in Siddha literature. Kalludaikudori Maththirai is a herbo mineral drug indicated for Kalladaippu Noi. Kalludaikudori Maththirai is used to remove the urinary stones from the urinary pathway. It contains four ingredients; puried Rasam (Mercury), puried Kanthakam (Sulphur), Vellai Saaranai (Boerhavia diffusa) and Sirupeelai (Aerva lanata). The aim of the study was to review the existing Siddha herbomineral formulation, 􀀂Kalludaikudori Maththirai'' with evidence from the text 'Siddha Vaidya Thiraddu''. The data were obtained from research articles and the globally accepted website such as PubMed, Medline, and Meddler. According to the pharmacological studies, the ingredients are very effective for anti-urolithiasis (Lithotriptic), diuretic and anti-inammatory activities. According to Siddha literature, the main ingredients of Kalludaikudori Maththirai consist of the action for elimination of vitiated Pittam. This review is an initial step towards, scientically analyzing 􀀂 Kalludaikudori Maththirai” in the management of Kalladaippu Noi.
Keywords: Kalladaippu; Kalludaikudori Maththirai; Urolithiasis